Features of the Course and Treatment of Conjunctivitis in Patients with Viral Infections, Including COVID-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Conjunctivitis is a disease of the organs of vision characterized by the development of a strong inflammatory process in the mucous membrane of the eye. Symptoms of the disease manifest themselves in the form of redness and swelling of the conjunctiva, eye discharge and increased photosensitivity. Almost anyone can experience conjunctivitis. This disease not only causes great discomfort, but is also dangerous for others. Therefore, to exclude any complications and infection of other people, it is necessary to treat the pathology competently.This is an inflammation of the connective membrane of the eye (conjunctiva), which covers the back surface of the eyelids and the eyeball up to the cornea. This connective membrane includes lymphatic and blood vessels, nerve fibers, and glands that secrete protective mucus.